PENGARUH VARIASI LATIHAN TERHADAP KEMAMPUAN SERVIS SISWA PUTRA EKSTRAKURIKULER SEPAKTAKRAW SMP N 1 KUBU KABUPATEN ROKAN HILIR - Rizal Efendi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to find find out if there is influence of exercise variation on servis skill of takraw extracurricular studients of SMPN 1 Kubu Rokan Hilir . The design of this study uses a group of the research is wearing the approach one group pretest-postest design, with population extracurricular students of SMPN 1 Kubu Rokan Hilir 15 people. The sample in this study, using a technique the total sampling are used is a sample of saturated and that’s where all the population as a sample. The instrument used pre-test and post-test with purposing to know the service skill of Takraw ectracurricular student. Process of data used statistic, to know the normality test with lilifors test on significance level α (0,05). Hypothesis was used there is the effect of exercise variation on service skill of takraw extracurricular student of SMPN 1Kubu Rokan Hilir. Based on the statistical data analysis, the data pre-test was 0.217 and post test was 0.167 and Ltabel 0.227 so the data was normal with increasing the score (d) was 2,48. Based on the analysis of T-test get 3,81 and T-table 1,76, it mean T-test > T-table. Hence, there is the effect of exercise variation on service skill of takraw extracurricular students of SMPN 1 Kubu Rokan Hilir.Key Words : Exercise variation, Takraw service skill